2020
DOI: 10.1002/ams2.585
|View full text |Cite
|
Sign up to set email alerts
|

Preventing thrombosis in a COVID‐19 patient by combined therapy with nafamostat and heparin during extracorporeal membrane oxygenation

Abstract: Background Extracorporeal membrane oxygenation (ECMO) can be life‐saving in cases of coronavirus disease (COVID‐19); however, circuit thrombosis is a complication. This report describes a COVID‐19 patient treated with nafamostat and heparin to prevent circuit thrombosis during ECMO support. Case presentation A 63‐year‐old man was transferred to our hospital with respiratory failure due to COVID‐19 pneumonia. He was provided venous‐venous ECMO to maintain oxygenation. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…NM, a synthetic serine protease inhibitor [32], has been used to treat pancreatitis and acute vasculitis clinically in Japan. NM has been recently shown to be beneficial for patients with coronavirus disease 2019 (COVID-19) in some case reports [33][34][35]. In our study, we found that NM promoted NK cell IFN-γ production in both direct and indirect manners.…”
Section: Discussionsupporting
confidence: 67%
“…NM, a synthetic serine protease inhibitor [32], has been used to treat pancreatitis and acute vasculitis clinically in Japan. NM has been recently shown to be beneficial for patients with coronavirus disease 2019 (COVID-19) in some case reports [33][34][35]. In our study, we found that NM promoted NK cell IFN-γ production in both direct and indirect manners.…”
Section: Discussionsupporting
confidence: 67%
“…[ 57 ] In fact, a report showed that combination therapy with nafamostat and heparin prevented circuit thrombosis in a COVID‐19 patient during extracorporeal membrane oxygenation. [ 58 ] Similarly, another study found that nafamostat improves COVID‐19 pneumonia in patients requiring supplementary oxygen therapy. [ 59 ] Altogether, these findings highlight a third dimension to beneficial role for treatment of COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, its anti-coagulant and anti-viral properties may help in the management of COVID-19 patients with coagulopathy (Asakura 2020). A case report demonstrated that the combination therapy with nafamostat and heparin is more efficient than heparin monotherapy in stopping circuit thrombosis during venous-venous extracorporeal membrane oxygenation [VV-ECMO] (Doi et al 2020a).…”
Section: Nafamostatmentioning
confidence: 99%